Prevalence of Hypertension Among Tribal Population in India: A Systematic Review and Meta-Analysis - Majgi, Sumanth; Suresh, Harshini; Nuggehalli Srinivas, Prashanth; Ahmed, Mansoor (National Journal of Community Medicine, 2023)
Hypertension is an important worldwide public-health challenge and it is accountable for 7% of Disability Adjusted Life Years (DALY) loss, and by the end of 2025 about 29% of world’s population is likely to suffer from hypertension. Tribal population constitute about 8% of the total population in India. Among tribal population, study on hypertension will provide an interesting outcome because studies across the world have shown a lower prevalence. The objective of the study was to estimate the pooled prevalence of hypertension among adult tribal populations in India and also to analyse the possible sources of heterogeneity in the estimate. A systematic search was performed in PubMed, Google scholar, Scopus, Embase MEDLINE, and journals for articles published between 2001 and 2020. This is a systematic review and meta-analysis done on hypertension among tribal populations of India. Three authors independently reviewed the articles, performed quality assessment and data was extracted. Pooled estimate of hypertension was calculated. Subgroup analyses was performed. A total of 26 articles with a total number of subjects of 75,543 were included in the study. The pooled estimate of hypertension prevalence was 25.1% (95% CI: 24.7, 25.4). There was significant heterogeneity among the studies (I2 = 98.2 and Q = 1289.37). It is essential to conduct larger cohort studies and randomised controlled trials to determine the causes of the increased prevalence of hypertension among the tribal population. The prevalence of hypertension among tribal population are essential as a source of primary information and for rational planning of health services and will help public-health policy-makers to assign sufficient priority and resources for its management and prevention.